Kondisi Sosial Ekonomi dan Nilai Tukar Nelayan di Desa Sanur Kaja, Denpasar, Bali - Setiarini, Ika; Restu, I Wayan; Kartika, I Wayan Darya (Current Trends in Aquatic Science; Vol 6 No 2 (2023), 2023)
Important aspects that affect the level of welfare and the economy of fishermen are the socio-economic conditions and exchange rates of fishermen. The purpose of this study was to determine the socio-economic conditions and exchange rates of fishermen in the Sanur Kaja Village. Primary data was obtained based on observations, interviews, and questionnaires on respondents (samples) by purposive sampling, which includes data on social aspects (age, education, number of family dependents, and variety of jobs) and data on economic aspects (fishery income, expenses, and non-fishery income). All data were analyzed using a qualitative and quantitative approach, namely data analysis for calculating Fishermen's Exchange Rates (NTN). Based on the data obtained, the age range of fishermen is 28 years to 61 years, with varying levels of education ranging from not having finished elementary school, elementary school, junior high school, high school, and Diploma to Bachelor with the number of family dependents ranging from 1 to 6 people. The income earned varies from < IDR. 200,000 to IDR. 750,000 with expenses starting from IDR. 100,000 to IDR. 200,000 on 1 time went to sea. Based on the calculation results, the NTN is above 1, which is 1.59. With NTN above 1, this means that fishermen are said to be able to fulfill their basic needs.